2008
DOI: 10.1007/s12010-008-8236-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Constant Glucose Feeding on the Production of Exopolysaccharides by Tremella fuciformis Spores

Abstract: A fed-batch culture system with constant feeding (glucose 80 g L(-1), 0.25 ml min(-1)) was used to study the influence of glucose on cell dry weight and exopolysaccharides production from submerged Tremella fuciformis spores in a 5-L stirred-tank bioreactor. The results showed that high levels of cell mass (9.80 g L(-1)) and exopolysaccharides production (3.12 g L(-1)) in fed-batch fermentation were obtained after 1 h of feeding, where the specific growth rate (mu) and exopolysaccharides yield on substrate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This data is in agreement with [25,56,57]. So the main source of carbon in the medium (glucose) was almost depleted, and fungus gets under the conditions of carbon starvation and is “searching” for the sources of carbon.…”
Section: Resultssupporting
confidence: 89%
“…This data is in agreement with [25,56,57]. So the main source of carbon in the medium (glucose) was almost depleted, and fungus gets under the conditions of carbon starvation and is “searching” for the sources of carbon.…”
Section: Resultssupporting
confidence: 89%
“…Fortunately, polysaccharides, the major group of bioactive ingredients in have been extracted and isolated not only from the basidiocarps, but also from mentation culture of the isolated strains [3,6]. Tremella species are heterogene there are two stages in their life cycle, the haploid yeast stage and the filam dikaryon stage; the haploid yeast stage is called tremellomycetous yeast [11][12][13] been found that the basidiospore of both T. fuciformis and T. aurantialba could re by budding and growing as haploid yeast cells [3,[14][15][16]. As it is easier to ac high-density cultivation and shorter production period for yeast, the cultivatio yeast form strain has been considered a more promising alternative for the lar production of polysaccharides from T. fuciformis [14][15][16] and T. aurantialba [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tremella species are heterogeneous and there are two stages in their life cycle, the haploid yeast stage and the filamentous dikaryon stage; the haploid yeast stage is called tremellomycetous yeast [ 11 , 12 , 13 ]. It has been found that the basidiospore of both T. fuciformis and T. aurantialba could reproduce by budding and growing as haploid yeast cells [ 3 , 14 , 15 , 16 ]. As it is easier to achieve a high-density cultivation and shorter production period for yeast, the cultivation of the yeast form strain has been considered a more promising alternative for the large-scale production of polysaccharides from T. fuciformis [ 14 , 15 , 16 ] and T. aurantialba [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation